The effect of hormonal contraception on symptoms associated with the menstrual cycle - Sobstyl, Anna; Sobstyl, Małgorzata; Chilimoniuk, Zuzanna; Łakota-Sipa, Magdalena; Borkowska, Aleksandra; Chałupnik, Aleksandra; Wertel, Iwona (Journal of Education, Health and Sport, 2019)
Nowadays, there exist a large number of methods that allow to prevent unintended pregnancy. One of the most common technique in Poland is hormonal contraception in the form of contraceptive pills. This method is effective, easy to use, and more importantly it does not cause permanent sterility. Moreover, hormonal contraception comes with plenty of additional health benefits that are not related to contraception alone, such as: reduction of menstrual pain, regular cycles and lack of menorrhagia. Due to the beneficial effect on the body, hormonal contraception is used in the treatment of certain diseases, such as acne and endometriosis. Reduction of numerous existing symptoms leads to an improvement in the quality of women’s lives.